2015
DOI: 10.3168/jds.2015-9361
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of the flavonol quercetin in neonatal calves after oral administration of quercetin aglycone or rutin

Abstract: Polyphenols, such as flavonoids, are secondary plant metabolites with potentially health-promoting properties. In newborn calves flavonoids may improve health status, but little is known about the systemically availability of flavonoids in calves to exert biological effects. The aim of this study was to investigate the oral bioavailability of the flavonol quercetin, applied either as quercetin aglycone (QA) or as its glucorhamnoside rutin (RU), in newborn dairy calves. Twenty-one male newborn German Holstein c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 51 publications
(82 reference statements)
0
24
1
Order By: Relevance
“…Thus, improvement of the antioxidant status in newborn calves may accelerate the maturation of their own immune system, improve health status, and thus reduce calf losses. In a previous study, we have shown that quercetin in newborn calves is bio-available when fed as quercetin aglycone or as rutin, a prerequest for systemic functioning of quercetin in the body (Maciej et al, 2015). Based on that, we have tested in the present study the hypothesis that quercetin and catechin supplementation affect metabolism and the antioxidative and health status during the first 4 wk of life in dairy calves.…”
Section: Short Communicationmentioning
confidence: 91%
See 2 more Smart Citations
“…Thus, improvement of the antioxidant status in newborn calves may accelerate the maturation of their own immune system, improve health status, and thus reduce calf losses. In a previous study, we have shown that quercetin in newborn calves is bio-available when fed as quercetin aglycone or as rutin, a prerequest for systemic functioning of quercetin in the body (Maciej et al, 2015). Based on that, we have tested in the present study the hypothesis that quercetin and catechin supplementation affect metabolism and the antioxidative and health status during the first 4 wk of life in dairy calves.…”
Section: Short Communicationmentioning
confidence: 91%
“…The calves had free access to pelleted concentrate (Kälber Start 18/3 Vollkraft Mischfutterwerke GmbH, Karstädt, Germany) and hay from d 4 on. Concentrate intake was measured daily after the morning milk feeding (Maciej et al, 2015).…”
Section: Short Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…From immunological stand point, diets rich in flavonoids, specifically quercetin, have positive health benefits, i.e., reduce infection risk, affect immunity and inflammation. Additionally, solid evidence also suggests that quercetin ultimately benefits in promoting growth and performance and improved feed efficiency in livestock (Gohlke et al, 2013;Maciej et al, 2015;Stoldt et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…One of spotlight herbal phenolic substances is quercetin, which is found in many edible plants, fruits and vegetables (Erlund, 2004;Formica et al, 1995). The bioavailability studies of quercetin and its metabolites; aglycone and rutin, in cows demonstrated that quercetin can be absorbed via digestive tracts and eventually entered the plasma (Berger et al, 2012;Gohlke et al, 2013;Maciej et al, 2015). Several in vivo studies of quercetin in neonatal calves, periparturient and lactating cows, in the aspects of bovine health and production, have been recently reported (Gohlke et al, 2013;Maciej et al, 2015;Stoldt et al, 2015); however, another point of view remains scarce in bovine innate immunity.…”
Section: Introductionmentioning
confidence: 99%